Analysis of Export Strategies on Apple Fruit Juice at Pt Batu Bhumi Suryatama - David Rivaldy Hermanto; Qonitah Lutfatullaili; Liem Gai Sin; Juan Jose Zuluaga (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
This study analyzes the effectiveness of the promotion strategy for PT Batu Bhumi Suryatama Sari Apel which is engaged in packaged apple juice. This research is very important for companies because with a good promotion strategy can increase sales. Because the system is not analyzed, this study intends to conduct an analysis. This study uses the interview method as a data collection technique and uses qualitative methods to analyze data. PT Batu Bhumi Suryatama in conducting promotions, using social media namely Facebook and Instagram. After successfully exporting, PT Batu Bhumi Suryatama found its responsibility as a criticism from the exporting country. The criticism is about product packaging. Therefore, it can be said that it is very important to always remember that by simply selling packaging products, it is very important in relation to brand trust. But PT Batu Bhumi is able to maintain a preferred quality even though the price is high which causes very heavy to compete. Keywords: Promotion Strategy, Export, Obstacles, Packaging.